Civil Commitment in the Psychiatric Emergency Room: III. Disposition as a Function of Mental Disorder and Dangerousness Indicators - Segal, Steven P. (Arch Gen Psychiatry, 1988)
In 251 evaluations observed in five California public psychiatric emergency rooms, patients who were retained, whether new to the system or having histories of hospitalization, rated higher on measures of danger to self, danger to others, and grave disability than patients who were released. They were also more severely symptomatic and more often given major diagnoses. The combination of dangerousness and mental disorder predicted disposition for 93% of new patients and 88% of recidivist patients. Impulsivity was the most influential aspect of mental disorder.